2015
DOI: 10.1186/s12889-015-1479-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of unstable housing on all-cause mortality among persons who inject drugs

Abstract: BackgroundIllicit drug injecting is a well-established risk factor for morbidity and mortality. However, a limited number of prospective studies have examined the independent effect of unstable housing on mortality among persons who inject drugs (PWIDs). In this study we sought to identify if a relationship exists between unstable housing and all-cause mortality among PWIDs living in Vancouver, Canada.MethodsPWIDs participating in two prospective cohort studies in Vancouver, Canada were followed between May 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 24 publications
(28 reference statements)
1
42
0
Order By: Relevance
“…Additionally, PWID systemically experience disproportionate levels of homelessness [9,25*,29], untreated mental health comorbidities [37], polysubstance use [32] (including alcohol use [33]), and lower levels of healthcare engagement [9], all of which shape access and adherence to ART, as well as progression to AIDS and death. Additionally, incarceration [1**,43] and personal violence [3**,7,10*] remain persistent issues among HIV-positive PWID, with research demonstrating increased rates of suicides [7,44] being independently associated with a history of IDU (adjusted hazard ratio: 3.95; confidence interval: 1.99 – 7.86) [44].…”
Section: Hiv/aids-related Mortality In the Modern Treatment Eramentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, PWID systemically experience disproportionate levels of homelessness [9,25*,29], untreated mental health comorbidities [37], polysubstance use [32] (including alcohol use [33]), and lower levels of healthcare engagement [9], all of which shape access and adherence to ART, as well as progression to AIDS and death. Additionally, incarceration [1**,43] and personal violence [3**,7,10*] remain persistent issues among HIV-positive PWID, with research demonstrating increased rates of suicides [7,44] being independently associated with a history of IDU (adjusted hazard ratio: 3.95; confidence interval: 1.99 – 7.86) [44].…”
Section: Hiv/aids-related Mortality In the Modern Treatment Eramentioning
confidence: 99%
“…However, Joseph and colleagues [45] demonstrated that even in a setting with free access to HIV care, becoming non-adherent was associated with periods of homelessness, active IDU, and incarceration. In the same setting, Zivanovic and colleagues [25*] found that after adjusting for confounders such as HIV infection and drug use patterns, housing instability was independently associated with all-cause mortality in a cohort of PWID. This research highlights the need to consider contextual factors in the design of HIV care and treatment to PWID beyond treatment access, extending to the provision of basic subsistence needs, including supportive housing.…”
Section: Hiv/aids-related Mortality In the Modern Treatment Eramentioning
confidence: 99%
See 1 more Smart Citation
“…While acute-toxicity is common, other causes of premature death are prevalent among PWID as well, including but not limited to accidents [5], suicide [8, 9], and HIV-related mortality [10, 11]. Research has also identified important predictors of all-cause and acute-toxicity mortality relevant to PWID, such as sex work [12], unstable housing and/or homelessness [13], polydrug use [14, 15], bisexual orientation [16], and exiting methadone or other drug replacement treatment modalities [17, 18]. PWID also experience increased risk of acute-toxicity mortality after release from incarceration [19, 20] and male gender is commonly identified as a mortality risk factor [21].…”
Section: Introductionmentioning
confidence: 99%
“…18 Similarly, unstable housing is a well-documented independent risk factor for mortality in adult populations. 16, 1921 Some of us found unstable housing to be an independent risk factor for initiation into injection drug use among street-involved youth in Vancouver. 22 This highlights the importance of ensuring youth have economic security and stable housing.…”
Section: Introductionmentioning
confidence: 99%